Environmental Crisis in the Drama Script “Bumi Sudah Tua” by Ajeng Illa: A Literary Ecology Study - Dewi, Tiara Shafira (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This article aims to analyze the drama script “Bumi Sudah Tua” through the lens of literary ecology using a descriptive qualitative method. The research focuses on the portrayal of the relationship between humans and nature, and how this relationship is represented in the drama text. The background of this study stems from increasingly urgent environmental issues that demand deep reflection through artistic works, including drama.The main objective of this analysis is to identify and interpret ecological elements in the script, as well as to uncover the moral messages and social critiques it contains. The method used is descriptive qualitative, applying the principles of literary ecology. The data analyzed includes character dialogues, narrative passages, and setting descriptions relevant to ecological issues.The theory of literary ecology is used as the analytical framework to understand how the script represents the interaction between humans and the environment, and how ecological values (or the absence thereof) are reflected in character behavior and the storyline. The analysis process involves identifying ecological elements, interpreting symbolic meanings, and synthesizing findings to formulate conclusions.The results of the study show that the script “Bumi Sudah Tua” effectively depicts environmental degradation as a consequence of human greed and apathy.